2018
DOI: 10.1093/nar/gky941
|View full text |Cite
|
Sign up to set email alerts
|

YeastRGB: comparing the abundance and localization of yeast proteins across cells and libraries

Abstract: The ability to measure the abundance and visualize the localization of proteins across the yeast proteome has stimulated hypotheses on gene function and fueled discoveries. While the classic C’ tagged GFP yeast library has been the only resource for over a decade, the recent development of the SWAT technology has led to the creation of multiple novel yeast libraries where new-generation fluorescent reporters are fused at the N’ and C’ of open reading frames. Efficient access to these data requires a user inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 28 publications
5
45
0
Order By: Relevance
“…Rgd1, a RhoGAP for Rho3 and Rho4, has been shown to localize to polarized vesicles consistent with post-Golgi secretory vesicles (Lefèbvre et al, 2012;Doignon et al, 1999). Rgd2, a RhoGAP for Cdc42 and Rho5, localized to the bud tip in a high-throughput genomic screen (Dubreuil et al, 2018;Roumanie et al, 2001). Here we show that Rgd3 is a RhoGAP for Rho3 and Cdc42, and that it is associated with polarized vesicles.…”
Section: Discussionsupporting
confidence: 62%
“…Rgd1, a RhoGAP for Rho3 and Rho4, has been shown to localize to polarized vesicles consistent with post-Golgi secretory vesicles (Lefèbvre et al, 2012;Doignon et al, 1999). Rgd2, a RhoGAP for Cdc42 and Rho5, localized to the bud tip in a high-throughput genomic screen (Dubreuil et al, 2018;Roumanie et al, 2001). Here we show that Rgd3 is a RhoGAP for Rho3 and Cdc42, and that it is associated with polarized vesicles.…”
Section: Discussionsupporting
confidence: 62%
“…This gene was shown to be induced by Aro80 in the presence of AAAs (21) but its role has never been uncovered. Its cellular localization is not clear according to YeastRGB (26), but one high throughput dataset suggested that Esbp6 is located in the cell periphery (27). Furthermore, an overexpression mutant of ESBP6 was shown to confer tolerance to 6% lactic acid (28).…”
Section: Resultsmentioning
confidence: 99%
“…One interesting example is the N-terminal IDR in putative mitochondrial protein SHH3, which we predict to be associated with the mitochondrion, as well as the mitochondrial inner membrane. Indeed, SHH3 assumes what looks to be a mitochondrial localization in recent localization collections such as the LoQAtE (Localization and Quantitation Atlas of the yeast proteomE) database (Breker et al, 2014(Breker et al, , 2013 and Yeast RGB (Dubreuil et al, 2019). Another interesting case is an IDR in MFG1, which FAIDR predicts to be associated with sequence-specific DNA binding ( Figure 4A), indicating that MFG1 could be a transcription factor.…”
Section: Inferring Function For Specific Idrs In Uncharacterized Protmentioning
confidence: 99%